Modelo matemático de un reactor de lecho fijo para el proceso de pirólisis del cuesco de palma aceitera (2022)
In the present degree work, a mathematical model was carried out where the profiles were estimated. of temperature and concentration for biomass, the study that was developed throughout the document is based on the husk of palm oil, this is a by-product with few uses at the industry, therefore, the pyrolysis process was proposed in order to provide added value and reducing emissions generated by different alternative processes of this matter. This by-product is obtained from the direct extraction of palm oil. In the first instance, A bibliographical study was carried out with the objective of obtaining information on the process thermochemical in research, in addition to conducting a search focused on the equations of government and kinetic models that adapt to the process, in this way it was analyzed that the closest biomass with respect to the structural composition that corresponds to its content of cellulose, lignin, hemicellulose, and its elemental composition which is hydrogen, carbon, oxygen, nitrogen and sulfur, is the beech wood, because it presented similarities with the oil palm shell